Top2btm symposium on health care for men who have sex with men (MSM) - K Rebe; G de Swardt; H Struthers; J A McIntyre (AOSIS, 2011)
Men who have sex with men (MSM) are at high risk of HIV acquisition and transmission, and country-specific HIV prevalence rates are always higher in MSM than among heterosexual men. South African data confirm this, with reported HIV prevalences of 10.4 - 33.9% across various studies. Donors and government health planners have recognised the need for targeted programmes that address the high burden of HIV transmission and disease in stigmatised populations such as MSM, as well as other 'most at risk populations' (MARPS) such as commercial sex workers, drug users and displaced refugees. Specific programmes targeting MSM and other MARPS have been included in the South African government's current National Strategic Plan for health care and will feature in the new plan under development.